Pemberdayaan Ekonomi Masyarakat Melalui Pengembangan Potensi Lokal Di Kampung Tablasupa Distrik Depapre Kabupaten Jayapura - Transna Putra Urip (UNIVERSITAS CENDERAWASIH, 2019)
This community service aims to provide an understanding of the potential of the local economy. By providing knowledge and empowering businesses based on the local potential in motivating the community to develop their creativity in developing their local resources, through increasing the creativity of the community's economic business based on local potential. Through, identified local potentials in the regian, such as 1) coastal tourism potential, namely Harlem, Amai, Sarebo and Kitikipa and Tablasupa village settlements as separate tourism objects 2) capture and aquaculture 3) plantations 4) livestock and 5) mining and 6) industry pure coconut oil ( VCO). The empowerment of strategy that needs a comprehensive strategy with the concepts of micro, mezo and macro.